Iterative integration of TTEthernet network flows. (8th January 2020) - Beji, Sofiene; Hamadou, Sardaouna; Mullins, John; Gherbi, Abdelouahed
TTEthernet has been proposed as an improvement of the Ethernet network protocol to ensure communication of critical systems. Some of these systems, such as avionics systems, are complex and evolving ones. Therefore, they are designed iteratively by integrating in each iteration some components of the system. Adding new functionalities may induce substantial additional costs of reconfiguration of the system in order to meet the real-time requirements. Based on the constraint programming techniques, we develop in this paper a cost optimisation approach that meets the TTEthernet specification and validates the latencies requirements in an accurate way. We illustrate our approach on a case study with the MiniZinc tool (Nethercote et al., 2007).